Antimicrobial factors in the exudates of skin windows in human subjects. - McClelland, D B (1976)
The "skin window" technique in which the horny layer of the skin is abraded with a high speed grinder has been used to study the appearance of proteins with antimicrobial activity in the fluid accumulating in damaged human skin. The fluid was absorbed into paper discs and protein levels measured by radial diffusion. The skin exudates contained about 45% as much IgG and IgM as the subjects' serum, but the amount of IgA (68% of the serum level) in the exudate was significantly greater, suggesting selective transport into the lesion. The fluid also contains complement proteins, lysozyme and lactoferrin. The methods used in this study may provide useful information about clinical situations in which susceptibility to cutaneous infection is increased.